Perilaku kuat tarik bahan geotekstil teranyam dan nir-anyam - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Psikologi Universitas Gadjah Mada, 1998)
ABSTRACT Soil is comprised of graded particle materials that generally has a very, low tensile strength. Its bearing capacity to compressive load is also limited. Soil will slide, settle or collapse if the imposed external forces exceed its bearing capacity. To improve these weaknesses, soil reinforcement has been used especially to increase the tensile strength. Therefore, further study is required to select appropriate materials for soil reinforcement such as geotextile. For this reason, tensile tests in laboratory need to be carried out to study the tensile strength of geotextile and its behaviours in sustaining tensile load physically and mechanically. Moreover, this research is also carried out to study the appropriate direction of geotextile sheets to optimize the application. This research show that not all of geotextile materials can be applied as reinforcement. This is because they have different stress-strain behaviours that depend on the composition and the processing of the materials. Therefore, appropriate geotextile materials must be carefully selected for the applications of soil reinforcement to guarantee the stability of structures.